2008
DOI: 10.1007/s00421-008-0859-7
|View full text |Cite
|
Sign up to set email alerts
|

Vestibulo-ocular reflex and motion sickness in figure skaters

Abstract: In order to determine the effect of figure skating on the functional plasticity of the vestibular system, we quantified vestibulo-ocular reflex (VOR) and motion sickness (MS) intensity in 11 female figure skaters and 11 matched control subjects. Vestibular stimulation consisted of three cycles of sinusoidal rotation (0.025 Hz, +/-60 degrees /s) and two velocity steps of 60 degrees /s (acceleration 60 degrees /s(2)). Nauseogenic stimulation consisted of a constant velocity (60 degrees /s) off vertical axis rota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
34
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 25 publications
(38 reference statements)
5
34
0
Order By: Relevance
“…Similar results were seen in judo players, who develop positive motor skills to improve their postural balance from technical movements in unipodal support 23 . Furthermore, some authors suggested that athletes in combat sports such as karate (martial art similar to TKD) would maximize the changes in visual information to maintain upright standing [25][26][27] . Thus, TKD training may improve the ability to use the visual system to maintain balance 26,27 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar results were seen in judo players, who develop positive motor skills to improve their postural balance from technical movements in unipodal support 23 . Furthermore, some authors suggested that athletes in combat sports such as karate (martial art similar to TKD) would maximize the changes in visual information to maintain upright standing [25][26][27] . Thus, TKD training may improve the ability to use the visual system to maintain balance 26,27 .…”
Section: Discussionmentioning
confidence: 99%
“…Such training involves acrobatic jump and spinning kicks, which would stimulate the vestibular system and increase its sensitivity 27 . Fong et al 22 found that TKD training speeds up the development of vestibular function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The VOR allows a stable image to form when the head is moving, which is important to balance regulation (4). Linear accelerations are sensed by the utricle and saccule, while angular accelerations are sensed by fluid movement in each of three semicircular canals (one semicircular canal for each rotational axis: x, y and Cadence M. Baker 1 z) (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…23,26,32 Problems in the modulation and integration of sensory input coming from the vestibular, proprioception, visual and auditory systems may reduce motor performance, and mainly balance and manual dexterity. 33 The relationship between deficiencies in sensory processing and impaired motor control due to possible mutual neurodevelopmental underlying mechanisms may be supported by fact that SPD is highly prevalent among other co morbidities of DCD such as ADHD.…”
mentioning
confidence: 99%